Effectiveness of a Web-Based Educational eHealth Platform on Women’s Health Literacy About Phthalate Exposure: Randomized Controlled Trial - Ya Ling Shih; Shu Ching Wu; Pei Shan Li; Chia Jung Hsieh; Chieh-Yu Liu (Journal of Medical Internet Research, 2026)
Abstract Background Phthalates are environmental endocrine-disrupting chemicals widely used in plastics, cosmetics, food packaging, and personal care products. Women may experience frequent exposure through everyday consumer and household products. Improving phthalate-related health literacy may support informed exposure-reduction decisions; however, conventional health education provides limited opportunities for repeated, interactive, and individually tailored learning. Objective This randomized controlled trial evaluated the effectiveness of an eHealth educational intervention (Phthalates Free) in improving women’s overall and domain-specific phthalate-related health literacy and examined the association between platform engagement and health literacy outcomes. Methods A double-blind randomized controlled trial was conducted in the outpatient department of a regional teaching hospital in Taipei, Taiwan. A total of 114 women were randomly assigned to an intervention group (n=58) receiving a 6-month eHealth platform–based education program and a control group (n=56) receiving conventional paper-based education. Assessments were conducted at baseline (T0), 3 months (T1), and 6 months (T2). The Phthalate Health Literacy Scale (10 items; α =.90, content validity index=0.93) measured overall and domain-specific literacy (health care, disease prevention, and health promotion). Longitudinal outcomes were analyzed using generalized estimating equations based on all available observations according to participants’ original randomized assignments, with adjustment for waist circumference and pregnancy history. Analysis of covariance (ANCOVA) was used to compare 6-month outcomes after adjustment for baseline scores. Platform engagement and perceived usability were assessed using back-end analytics and the System Usability Scale (SUS). Results At 6 months, the intervention group showed a significantly greater increase in total health literacy than the control group (+9.93 points, Wald χ ² 1 =17.74; P